(untitled) (Ustozlar uchun, 2025)
The origins of English literature go back to the Anglo-Saxon period, which lasted from the 5th to the 11th century. During this time, Old English became the language of both poetry and prose. These early writings reflect the life, beliefs, and culture of the Anglo-Saxon people. The combination of pagan traditions and Christian influence created a unique literary style that became the foundation of later English literature.